2008
DOI: 10.1073/pnas.0710285105
|View full text |Cite
|
Sign up to set email alerts
|

Specific requirement of the chromatin modifier mSin3B in cell cycle exit and cellular differentiation

Abstract: The Sin3-histone deacetylase (HDAC) corepressor complex is conserved from yeast to humans. Mammals possess two highly related Sin3 proteins, mSin3A and mSin3B, which serve as scaffolds tethering HDAC enzymatic activity, and numerous sequence-specific transcription factors to enable local chromatin regulation at specific gene targets. Despite broad overlapping expression of mSin3A and mSin3B, mSin3A is cell-essential and vital for early embryonic development. Here, genetic disruption of mSin3B reveals a very di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
153
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(164 citation statements)
references
References 30 publications
11
153
0
Order By: Relevance
“…Total RNA was extracted and purified from the intestine of E18.5 embryos and subjected to reverse transcription with a QuantiTect kit (Qiagen). The resulting cDNA was subjected to real-time PCR analysis as described previously (53), with 200 nM primers specific for E2F1 (54) or GAPDH (53). The abundance of E2F1 mRNA was normalized relative to that of GAPDH mRNA.…”
Section: Immunoprecipitation (Ip) and Immunoblot Analysis (Ib)mentioning
confidence: 99%
“…Total RNA was extracted and purified from the intestine of E18.5 embryos and subjected to reverse transcription with a QuantiTect kit (Qiagen). The resulting cDNA was subjected to real-time PCR analysis as described previously (53), with 200 nM primers specific for E2F1 (54) or GAPDH (53). The abundance of E2F1 mRNA was normalized relative to that of GAPDH mRNA.…”
Section: Immunoprecipitation (Ip) and Immunoblot Analysis (Ib)mentioning
confidence: 99%
“…We have recently demonstrated that mouse embryonic fibroblasts genetically inactivated for Sin3B are refractory to quiescence as well as oncogene-induced senescence (33)(34)(35). In addition, SIN3B levels are significantly upregulated in preneoplastic senescent lesions in a mouse model of PDAC (34).…”
Section: Introductionmentioning
confidence: 99%
“…Using this approach, we demonstrate here that the inactivation of Sin3B in the pancreas prevents oncogenic KRAS-induced senescence, correlating with a defect in the proinflammatory phenotype, ultimately resulting in delayed pancreatic cancer progression. tional allele were first crossed with transgenic mice expressing the Cre recombinase under the control of the pancreas-specific p48 promoter (35,36). Sin3B flox/+ p48-Cre + and Sin3B flox/-p48-Cre + animals (hereafter referred to as Sin3B p+/-and Sin3B p-/-) were born at the expected ratio (data not shown).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ICM derived from these embryos shows severely retarded proliferation ex vivo [168]. Sin3b null embryos show defects in erythrocyte and granulocyte maturation and in skeletal development [170]. The Class III HDACs, known as Sirtuins (SirTs), are also implicated during differentiation and mammalian development [171].…”
Section: Histone Deacetylasesmentioning
confidence: 99%